New lineages of photobionts in Bolivian lichens expand our knowledge on habitat preferences and distribution of Asterochloris algae - Kosecka, Magdalena; Guzow-Krzemińska, Beata; Černajová, Ivana; Škaloud, Pavel; Jabłońska, Agnieszka; Kukwa, Martin (Scientific reports, 2021)
We studied the biodiversity of Asterochloris photobionts found in Bolivian lichens to better understand their global spatial distribution and adaptation strategies in the context of a worldwide phylogeny of the genus. Based on nuclear ITS rDNA, the chloroplast rbcL gene and the actin type I gene we reconstructed a phylogenetic tree that recovered nine new Asterochloris lineages, while 32 Bolivian photobiont samples were assigned to 12 previously recognized Asterochloris lineages. We also show that some previously discovered Asterochloris photobiont species and lineages may occur in a broader spectrum of climatic conditions, and mycobiont species and photobionts may show different preferences along an altitude gradient. To reveal general patterns of of mycobiont specificity towards the photobiont in Asterochloris, we tested the influence of climate, altitude, geographical distance and effects of symbiotic partner (mycobiont) at the species level of three genera of lichen forming fungi: Stereocaulon, Cladonia and Lepraria. Further, we compared the specificity of mycobionts towards Asterochloris photobionts in cosmopolitan, Neotropical, and Pantropical lichen forming fungi. Interestingly, cosmopolitan species showed the lowest specificity to their photobionts, but also the lowest haplotype diversity. Neotropical and Paleotropical mycobionts, however, were more specific.
Keywords: symbióza; Biodiversity; Chlorophyta; Phylogeny; ekosystém; Lichens; biodiverzita; Symbiosis; lišejníky; Bolivia; Bolívie; Ecosystem; fylogeneze